Translating impoliteness - literature review, translation challenges, and translation strategies in cross-cultural communication - Yang, Wei; Syed Abdullah, Syed Nurulakla; Ang, Lay Hoon; Yang, Mingxing (Springer Nature, 2025)
In recent years, research integrating translation studies with impoliteness has steadily increased, significantly contributing to the interdisciplinary development of both fields. However, there remains a lack of reviews that examine how impoliteness is translated across languages and cultures, particularly from a pragmatic standpoint. This study addresses this gap by providing a focused literature review of translation studies on impoliteness, centered on current research trends, methodologies, and analytical perspectives. Twenty-one articles published between 1998 and 2023 were selected from the Scopus and Science Direct databases, focusing on translation studies and impoliteness. Analysis of these studies reveals that cultural differences represent a primary challenge when translating impoliteness. In response, strategies such as euphemism and omission are commonly adopted, often resulting in a dilution of the original pragmatic force. The findings of this study aim to guide future interdisciplinary research on translation studies and impoliteness for translators and researchers, highlighting key challenges and practical strategies in translating impoliteness across cultural boundaries.